2007
DOI: 10.1210/me.2007-0051
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Maturation of Glycoprotein Hormone Free α-Subunit (GPHα) and GPHαα Homodimers

Abstract: The dynamics of glycoprotein hormone alpha-subunit (GPHalpha) maturation and GPHalpha alpha homodimer formation were studied in presence (JEG-3 choriocarcinoma cells) and absence (HeLa cells) of hCGbeta. In both cases, the major initially occurring GPHalpha variant in [35S]Met/Cys-labeled cells carried two N-glycans (M(r app) = 22 kDa). Moreover, a mono-N-glycosylated in vivo association-incompetent GPHalpha variant (M(r app) = 18 kDa) was observed. In JEG-3 cells the early 22-kDa GPHalpha either associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…Both the hCG␣/␣ and hCG␤/␤ homodimer are biological stable and activate the LH/CG receptor specifically. Additionally, the homodimers can stimulate the signal transduction to the same extent as hCG heterodimers (73)(74)(75)(76). Thus, we assume that Treg migration observed to the ␣-or ␤-subunit alone might be a result of the homodimerization of these subunits followed by an activation of the LH/CG receptor on the Treg.…”
Section: Discussionmentioning
confidence: 98%
“…Both the hCG␣/␣ and hCG␤/␤ homodimer are biological stable and activate the LH/CG receptor specifically. Additionally, the homodimers can stimulate the signal transduction to the same extent as hCG heterodimers (73)(74)(75)(76). Thus, we assume that Treg migration observed to the ␣-or ␤-subunit alone might be a result of the homodimerization of these subunits followed by an activation of the LH/CG receptor on the Treg.…”
Section: Discussionmentioning
confidence: 98%
“…The free α subunit differs from that associated in GPH heterodimers by presenting additional saccharide branching resulting in a slightly heavier molecular mass ( 104 , 105 ). Homodimers of the α subunit were characterized in both β subunit producing and non-producing cells ( 106 ). The α subunits are more tightly associated in the α homodimer than in the heterodimers ( 106 ).…”
Section: Unconventional Actions Of Gphs or Their Subunitsmentioning
confidence: 99%
“…Homodimers of the α subunit were characterized in both β subunit producing and non-producing cells ( 106 ). The α subunits are more tightly associated in the α homodimer than in the heterodimers ( 106 ). While the synthesis of large excess of α subunit allows the regulation of the heterodimer production to rely on the rate-limiting β subunit, the released free, heavily glycosylated α subunit may also serve other purposes and possibly, play a role by itself.…”
Section: Unconventional Actions Of Gphs or Their Subunitsmentioning
confidence: 99%
“…C, C-terminus; N, N-terminus. [38][39][40][41] In addition to the heterodimeric nature of the hormones, homodimers have also been found for LHβ, 42,43 and for the α subunit. [28][29][30][31][32] Moreover, it was posited that subunit association occurred before the seatbelt was latched by closure of Cys26 and Cys110.…”
Section: Folding and Assemblymentioning
confidence: 99%
“…exchange occurs during the maturation process and that subunit association occurred before completion of protein folding and disulfide formation. 40,41,44 Whether these homodimeric forms of the glycoprotein hormones have any associated bioactivity remains to be shown, although it has been reported that the free α subunit potentiates progesterone-mediated decidualization. In contrast to these reports, a different mechanism in which subunit assembly involved closure of the seatbelt latch, followed by threading of α loop 2, has been proposed.…”
Section: Folding and Assemblymentioning
confidence: 99%